Association of muscle fiber type with measures of obesity: A systematic review. (15th March 2022) - Damer, Alameen; El Meniawy, Sherif; McPherson, Ruth; Wells, George; Harper, Mary‐Ellen; Dent, Robert
Summary: Obesity derives from an extended period of positive energy imbalance due to a complex interplay of environmental and biological factors. Muscle fiber type and physiology have been hypothesized to affect metabolism and energy expenditure and thus to affect an individual's propensity to gain weight. However, there have been conflicting reports regarding a relationship between muscle fiber type and obesity. Here, we systematically reviewed literature investigating this topic from PubMed, Web of Science, and EMBASE. Of these, 32 articles were included in our final review and analysis. Most studies (22/32) reported a significant relationship between muscle fiber‐type proportion and a measure of obesity. Overall, there was a significant negative relationship between the proportion of type I fibers and body mass index (BMI) and a significant positive relationship between the proportion of type IIX fibers and BMI. Moreover, between‐group comparisons indicated a greater prevalence of type IIX fibers and a lower prevalence of type I fibers in patients living with obesity relative to lean individuals. These significant relationships were confirmed in a meta‐analysis of these data. The causal nature of these associations remains to be evaluated.